VD_FINDINFO Décision / 2023 / 127 vom 8. Februar 2023 - VD Tribunal cantonal (2023)
REJET DE LA DEMANDE, JUGEMENT PAR DÉFAUT, DÉLAI DE GARDE, RETARD | 368 al. 1 CPP (CH), 368 al. 3 CPP (CH), 85 al. 4 let. a CPP (CH)